IMPLANTAÇÃO DE SERVIÇO ESPECIALIZADO EM SAÚDE DA MULHER POR PARCERIA ENTRE INSTITUIÇÃO FORMADORA EM SAÚDE E SUS LOCAL: AMPLIAÇÃO DE ACESSO E CAMPO DE PRÁTICA PARA FORMAÇÃO EM SAÚDE - Piton Serra, Kátia; Padilha, Alexandre; Moura França, Jhenifer Nataly; Siqueira Guida, José Paulo; de Menezes Succi, Guilherme (InterAmerican Journal of Medicine and Health, 2022)
Objective: To describe a partnership experience between a health training institution and a local SUS network to implement a specialized comprehensive health service for women. Methods: descriptive study approved by the research ethics committee. Data collection was carried out between January 1, 2017 and December 5, 2019. A database was made with the services and procedures performed at the Outpatient Clinic BEM (Base of Excellence for Women) during the studied period. Tables of absolute numbers and frequency were made to describe the data found. Results: 3,676 cases were evaluated. Of these, 2,006 (54.6%) were scheduled for care at BEM, 1,232 (33.5%) were referred to other specialized care services and 438 (11.9%) were referred to the Basic Health Unit with care guidelines to be performed in primary care. By specialty, 2,459 (66.9%) consultations were performed in Gynecology, 760 (20.7%) in Obstetrics and 457 (12.4%) in Mastology. 687 ultrasound exams, 885 cardiotocography exams and 528 colposcopies were performed. 201 copper Intrauterine Devices were inserted, 528 colposcopies and 209 biopsies were performed. There were 5 courses in continuing education. Conclusion: the decision of the partnership between the educational institution and the local health network resulted in increased access and problem-solving capacity for women in this location.